HUBUNGAN MINAT SISWA BELAJAR BAHASA ARAB DENGAN STANDAR NASIONAL PENDIDIKAN DI MAN ACEH BARAT (The Correlation between Student’s Interest in Learning Arabic and National Education Standard at Islamic Senior High Schools in Aceh Barat)) - Dara Mubshirah (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2021)
Interest and national education standard are two important factors for students in learning Arabic language. The purpose of this study is to find out the correlation between the student's interest in learning Arabic and national education standards. This study used the correlational method. The data collection tools used questionnaire which was carried out on 130 students of MAN Aceh Barat and 3 Arabic teachers of MAN Aceh Barat. The data were analyzed by using chi-square with α= 0,05. The result of the study showed that there was relation between interest in learning Arabic and standard process at MAN Aceh Barat (P-value = 0,03), there was no relation between interest in learning Arabic and educational assessment standards at MAN Aceh Barat (P-value = 0,182).